2002
DOI: 10.1021/ie010569o
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Reaction of Halon 1301 (CBrF3) with Propane

Abstract: The nonoxidative gas-phase reaction of Halon 1301 (CBrF3) with propane in a nitrogen bath was investigated using a tubular plug-flow reactor. Experiments were performed at atmospheric pressure, over a range of temperatures from 500 to 700 °C, and at residence times between 0.7 and 4 s. The pyrolysis of propane was also investigated to examine the effect of added Halon 1301 on the pyrolysis reaction. Experimental data suggest that CF3 and possibly Br radicals formed via the thermal cleavage of CBrF3 react with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The approach taken by various researchers to convert fluorocarbons to value-added materials primarily involves conventional thermal reactor based technologies. Previously, we have disclosed that fluorocarbons can be converted to a value-added material, vinylidene fluoride (VDF) in a thermal reactor. …”
Section: Introductionmentioning
confidence: 99%
“…The approach taken by various researchers to convert fluorocarbons to value-added materials primarily involves conventional thermal reactor based technologies. Previously, we have disclosed that fluorocarbons can be converted to a value-added material, vinylidene fluoride (VDF) in a thermal reactor. …”
Section: Introductionmentioning
confidence: 99%
“…Gas-phase reactions of halon 1301 with hydrogen, CH4 and C3H8 have been investigated recently by Li et al (8,9) and Yu et al (10). They have reported that hydrodehalogenation of halon 1301 with H2 or CH4 is a promising process for production of CHF3, which can be used as the precursor for production of CF3I (11), a replacement for halon 1301.…”
Section: Introductionmentioning
confidence: 99%
“…A relatively small number of studies on the gas-phase hydrodehalogenation of halons have been reported. [2][3][4][5][6][7] For example, Li et al studied the gas-phase hydrodehalogenation of CBrF 3 (halon 1301) with hydrogen and methane 3,4 and found that these reactions can be used to produce CHF 3 , a precursor for the synthesis of CF 3 I, 8 a promising halon replacement chemical.…”
Section: Introductionmentioning
confidence: 99%